THE IMPACT OF PKH ON THE WELFARE OF POOR PEOPLE IN MLANDINGAN FROM A SHARIA ECONOMIC PERSPEKTIVE - Silvi Nury Romadhoni; Mohammad Alief Hidayatullah (Profit: Jurnal Kajian Ekonomi dan Perbankan Syariah)
This study aims to analyze the impact of the Family Hope Program (PKH) on improving the welfare of poor communities in Mlandingan Village from the perspective of sharia economics. The method used is descriptive qualitative. The research was conducted in Mlandingan Village, Mlandingan District, Situbondo Regency, East Java, Indonesia. Data collection was carried out through direct interviews with PKH implementers and program beneficiaries. The results indicate that PKH positively impacts the welfare of poor people through three main principles in sharia economics: ta’awun (mutual assistance) encouraging social solidarity, al-‘adl (justice) reflected in fair and targeted aid distribution, and maslahah (public benefit) seen from increased access to education, health, and basic needs. It can be concluded that PKH has helped realize the welfare of poor communities in accordance with Islamic values or sharia economics